MOTIVASI SISWA MENGIKUTI MATA PELAJARAN PENJASORKES DI SMP NEGERI 9 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is based on the result of field observations of students are less active in studying sports physical and heath education, and students are still lazing, so don’t get excited in doing sports activities are taught, this is all due to lack of facilities and infrastructure and teacher’s learning methods are still pressing and quickly make students feel bored. Students motivation in the subjects of sports physical and heath education is the driving force within the phychic cause learning activities, ensure the continuity of learning in order to achieve the goal of learning subjects sports physical and health education and this is an important aspect of teaching and learning. Students who don’t have the motivation will not be trying very hard to learn and the otherwise, students who have a strong motivation will have a lot of energy for learning activities. This research is descriptive quantitative and conducted by survey. The research population was all students in grade VII totaling 323 peoples, which is 156 men and 167 women. Because the data is homogeneus, then the sample is determined graders VII.I totaling 36 peoples, which is 18 men and 18 womenn. Data were collected using a questionnaire, which prior field research, conducted prior trials. Data were analyzed using descriptive statistics and statistical inference. The result showed that the level of students motivetion in sports physical and healh education SMP Negeri 9 Pekanbaru is very high that the mean of 4,19 to 0,48 deviaal standarts. Meanwhile each indicator has contibuted to the motivation of students attending sports physical and health education in SMP Negeri 9 Pekanbaru which is the average contribution is 52,07%. Therefore, it is expected to teachers of sports physical and heath education to encourage and motivate the students, and students are expected to have a strong motivation to achievement.Keywords: motivation, learning, students.